Processed bed elevation picks from the POLARGAP radar survey across the Pensacola-Pole Basin (2015/2016) ... - Corr, Hugh; Ferraccioli, Fausto; Forsberg, Rene; Jordan, Tom; Kohler, Jack; Matsuoka, Kenichi; Olesen, Arne; Robinson, Carl (NERC EDS UK Polar Data Centre, 2021)
This dataset contains bed and surface elevation picks derived from airborne radar collected during the POLARGAP 2015/16 project funded by the European Space Agency (ESA) and with in-kind contribution from the British Antarctic Survey, the Technical University of Denmark (DTU), the Norwegian Polar Institute (NPI) and the US National Science Foundation (NSF). This collaborative project collected ~38,000 line-km of new aerogeophysical data using the 150MHz PASIN radar echo sounding system (Corr et al., 2007) deployed on a British Antarctic Survey (BAS) Twin Otter. The primary objective of the POLARGAP campaign was to carry out an airborne gravity survey covering the southern polar gap beyond the coverage of the GOCE orbit. This dataset covers the South Pole as well as parts of the Support Force, Foundation and Recovery Glaciers. The bed pick data acquired during the POLARGAP survey over the Recovery Lakes is archived at NPI: https://doi.org/10.21334/npolar.2019.ae99f750. ... : Radar data were collected using the 150-MHz PASIN radar echo sounding system operating in full polarimetric mode. Data provided here includes picks and derived elevations of the ice sheet surface and bed for the BAS-led part of this campaign, which includes the survey lines over the South Pole, as well as Support Force, Foundation and Recovery Glaciers. The radar data was processed using a coherent averaging filter (commonly referred to as unfocused Synthetic Aperture Radar (SAR) processing) with Doppler beam sharpening to enhance the signal to clutter ratio of the bed echo and improve visualisation. The received chirp of 4 microseconds, 12 MHz bandwidth data was compressed, filtered, and decimated from the original trace acquisition rate of 156.25 Hz to 2Hz, equivalent to ~30m in along-track spacing. The bed reflector was picked in a semi-automated manner within the seismic processing package ProMax. An automatic first break picker was applied initially, with subsequent manual editing/removal of picks which ...